Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s00264-006-0209-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcome assessment of bracing in adolescent idiopathic scoliosis by the use of the SRS-22 questionnaire

Abstract: The SRS-22 questionnaire is specifically designed for the assessment of quality of life in spinal deformity patients. This study is the first to use it to assess the quality of life of adolescent idiopathic scoliosis patients under brace treatment and compares the results with an observational group matched by age and curve magnitude. Forty-six patients were enrolled into each group. Overall, it was found that patients under observation had a significantly better quality of life than braced patients. Specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
2
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 18 publications
1
50
2
9
Order By: Relevance
“…The scores presentedespecially for satisfaction with management (2.25 ± 1.16 at baseline and 1.89 ± 0.84 during brace treatment) are clearly lower in comparison with other studies with scores of 3.8 ± 0.70 in 109 AIS patients after completion of treatment [5] and 3.55-4.03 in 46 AIS patients receiving brace treatment, depending on the size of the Cobb angles [7]. It is important to note that the scores reported in these publications were calculated in patients at an average of 24 and 27 months, respectively, after the start of brace treatment.…”
Section: Srs-22 Questionnairecontrasting
confidence: 65%
“…The scores presentedespecially for satisfaction with management (2.25 ± 1.16 at baseline and 1.89 ± 0.84 during brace treatment) are clearly lower in comparison with other studies with scores of 3.8 ± 0.70 in 109 AIS patients after completion of treatment [5] and 3.55-4.03 in 46 AIS patients receiving brace treatment, depending on the size of the Cobb angles [7]. It is important to note that the scores reported in these publications were calculated in patients at an average of 24 and 27 months, respectively, after the start of brace treatment.…”
Section: Srs-22 Questionnairecontrasting
confidence: 65%
“…The main finding of the current study was that the difference between average scores of QoL based on the SRS-22 questionnaire domains in the Milwaukee brace and TLSO groups were trivial and not significant. Cheung et al 4 using the SRS-22 questionnaire, compared a group of 46 patients treated with a Boston brace for a progressive curve with an age-and curve-matched group of 46 patients who were treated with observation (control group) to evaluate the effect of bracing on the QoL. It might be possible to consider the control group in the Cheung et al 4 study as a basis for comparison with the results of the current study.…”
Section: Discussionmentioning
confidence: 98%
“…Cheung et al 4 using the SRS-22 questionnaire, compared a group of 46 patients treated with a Boston brace for a progressive curve with an age-and curve-matched group of 46 patients who were treated with observation (control group) to evaluate the effect of bracing on the QoL. It might be possible to consider the control group in the Cheung et al 4 study as a basis for comparison with the results of the current study. The mean total score of the QoL in all of the participants in the current study was 3.65.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current study confirmed the predictive value of RVAD and CRVA for the effectiveness of bracing in early AIS patients. Moreover, measurements of initial RVAD and CRVA before bracing can help to more accurately identify patients who are at higher risk of curve progression, thus to refine the indications and the protocols of brace treatment, because of the potential drawbacks of brace treatment, such as affecting the quality of life [31], reducing the flexibility of the spine [32], and so on. In addition, serial measurements of RVAD and CRVA provide constant assessments of the risk of curve progression, which are certainly more accurate and more reliable than that the measurements at brace initiation.…”
Section: Role Of Rva Measurements In Predicting Curve Progressionmentioning
confidence: 99%